INTEGRASI PASAR SAHAM ASEAN-5: ANALISIS SEBELUM DAN SEPANJANG KRISIS KEUANGAN GLOBAL 2007-2008 - Endri, Endri (UNIVERSITY OF MERDEKA MALANG, 2010)
This article investigated both the static and dynamic inter dependence of the fivestock markets in the original Association of Southeast Asian Nations countries (ASEAN-5),namely Indonesia, Singapore, Malaysia, Thailand and Philippine. Using data from 2000-2008,the paper employed both correlation and co-integration analysis to describe the behavior ofthe above markets, both before and during 2007-2008 Global financial crisis. Examination ofstock market index, using correlation analysis revealed an increase in the interdependencies(increased correlation) across the Southeast Asian stock markets during the crisis. Multivari-ate co-integration tests showed that ASEAN-5 stock markets only had one significant co inte-gration vector along the crisis period. Along the full period there was one vector that signifi-cantly integrated or five common trends. This finding indicated the long time co-integrationamong the ASEAN-5 stock markets. On the other hand, along the global financial crisis noproof of long time co-integration was found among the ASEAN-5.